Codeless Deep Learning with KNIME : Build, train, and deploy various deep neural network architectures using KNIME Analytics Platform /: Build, train, and deploy various deep neural network architectures using KNIME Analytics Platform. (2020) - Melcher, Kathrin; Silipo, Rosaria
No abstract available